Toughened cellulose ionogels based on ion-shielding effect to enhance phase separation, methods of making, and uses thereof
Patent Information
- Application Number
- CN202610926773.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-09
AI Technical Summary
然而,随着硬相含量提高,离子凝胶的拉伸性能通常会被牺牲
(1)本发明以HPC为支撑骨架、锂离子诱导大尺度相分离,可协同调控离子凝胶的断裂强度(15.1 MPa),拉伸性(515%)和韧性(45 MJ m-3)。
Smart Images

Figure CN122878696A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the preparation of ion gels, and particularly to a strong and tough cellulose ion gel based on the ion shielding effect to enhance phase separation, its preparation method, and its application. Background Technology
[0002] Ion gels inherit the excellent conductivity, thermal stability, and low volatility of ionic liquids, making them a suitable candidate to replace hydrogels. However, the plasticizing effect of ionic liquids reduces the mechanical properties of ion gels, severely limiting their application and development. Especially in real-world scenarios involving intense motion or high-intensity sensing, ion gels are highly susceptible to structural damage, which can lead to signal attenuation or even complete malfunction. These harsh conditions impose stricter requirements on the mechanical properties of sensors. Several toughening strategies have been reported. One strategy involves introducing inorganic fillers into the ion gel system. These fillers have high specific surface areas and can interact with multiple polymer chains simultaneously, increasing network density and thus achieving a toughening effect. However, a key bottleneck in using inorganic additives to toughen ion gels lies in poor interfacial compatibility. This means that these additives not only fail to effectively toughen the gel but also introduce numerous structural defects, ultimately degrading its mechanical properties. Constructing sacrificial bonds is another toughening strategy. Its mechanism involves dissipating energy that could otherwise cause damage during material deformation, thereby inhibiting the fracture of the ion gel. While the breaking and reconstruction of physical bonds can enhance the self-healing properties of ionic gels, the improvement in mechanical properties through bond breaking alone is limited. Phase separation is an effective way to enhance ionic gels. By utilizing the compatibility differences between polymers and ionic liquids, a hard phase that repels the ionic liquid and a soft phase that adsorbs it can be formed; by controlling the content of these two phases, the strength of the ionic gel can be efficiently controlled. However, as the content of the hard phase increases, the tensile properties of the ionic gel are usually sacrificed. Therefore, how to control the phase separation structure to improve the strength and adhesion of the ionic gel without sacrificing its tensile ductility remains an important challenge.
[0003] Cellulose, as the most abundant natural renewable polymer, possesses unique advantages such as high modulus, ease of functionalization, and good biocompatibility. Furthermore, cellulose can be further entangled with polymer networks, thereby improving the mechanical properties of ionogels. The addition of salt ions to the polymer may cause the polymer chains to coil more easily due to the ion shielding effect, thus forming phase regions separated from other components, which can be used to effectively disperse stress in ionogels during deformation. However, precisely regulating the interactions between the polymer, ionic liquid, cellulose, and salt ions to achieve simultaneous improvement in efficient stress dissipation and interfacial adhesion still requires the introduction of new regulatory mechanisms to achieve a precise match between microstructure and macroscopic properties.
[0004] Based on this, this invention uses ethylene glycol as a solvent, HPC as a backbone, and acrylic acid and vinyl ionic liquids as polymer chains. By utilizing lithium ions to enhance the phase separation structure within the system, it achieves synergistic optimization of the mechanical properties, reversible adhesion properties, and ionic conductivity of the ionogel. The final prepared cellulose ionogel exhibits a fracture stress of 15.1 MPa, a fracture strain of 515%, and a fracture toughness of 45 MJ / m. -3 The adhesion strength reached 4.26 MPa. At the same time, the phase separation structure regulated by cellulose and lithium ions can optimize the ion transport channels, so that the ion gel has good sensing performance (GF= 1.41, reaction time 1.5-2 s) while improving mechanical properties. Summary of the Invention
[0005] To overcome the shortcomings of the prior art, this invention provides a strong and tough cellulose ion gel based on the ion shielding effect to enhance phase separation, its preparation method, and its application.
[0006] This invention is achieved through the following technical solution: In a first aspect, the present invention provides a tough cellulose ionic gel based on the ion shielding effect to enhance phase separation. The tough cellulose ionic gel is characterized in that it is prepared by ultraviolet-light free radical polymerization of monomeric components AA acrylic acid, 1-ethyl-3-vinylimidazolium tetrafluoroborate ionic liquid, ethylene glycol EG, hydroxypropyl cellulose HPC, lithium tetrafluoroborate, and a photoinitiator. The ionic gel uses HPC as a backbone and acrylic acid and vinyl ionic liquid as polymer chains, leveraging the ion shielding effect of lithium ions to strengthen the phase separation structure of the system, thereby achieving synergistic optimization of mechanical properties, adhesion properties, and conductive sensing properties.
[0007] Furthermore, the proportions of each raw material component are as follows: the mass ratio of acrylic acid to 1-ethyl-3-vinylimidazolium tetrafluoroborate is 6:2, the amount of HPC added is 0.25 wt% of the total mass of the system, the lithium ion concentration is 2M, and the molar concentration of lithium tetrafluoroborate is 2M.
[0008] Furthermore, the photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone.
[0009] Furthermore, the raw material components are as follows: ethylene glycol, the solvent, accounts for 33.33% of the total mass of the solute and solvent, that is, the mass ratio of ethylene glycol to the total mass of the solute ionic liquid IL and acrylic acid AA is 1:2; the concentration of lithium tetrafluoroborate is 2M; and the photoinitiator accounts for 1% of the total mass of AA + IL monomers. Furthermore, the raw material components are as follows: 3 g of AA, 1 g of 1-ethyl-3-vinylimidazolium tetrafluoroborate IL, 2 g of ethylene glycol, 0.015 g of HPC, 0.8 g of lithium tetrafluoroborate, and 0.04 g of photoinitiator.
[0010] Furthermore, the mechanical properties of the cellulose ion gel are as follows: fracture stress 15.1 MPa, fracture strain 515%, fracture toughness 45 MJ・m⁻³; it possesses anti-crack propagation, anti-torsion, anti-knotting, and anti-puncture properties, and the notched sample shows no obvious crack propagation at 300% strain.
[0011] Furthermore, the cellulose ion gel possesses temperature-controlled reversible adhesion properties. When heated to 60 °C and cooled to room temperature, it exhibits an adhesion strength of 4.26 MPa on a glass substrate. It also demonstrates adhesion capabilities on wood, iron sheets, PMMA (polymethyl methacrylate), and polytetrafluoroethylene substrates, maintaining an adhesion strength of 4 MPa after 50 adhesion cycles.
[0012] Furthermore, the cellulose ion gel has an electrical conductivity of 0.37 mS·cm⁻¹; when used as a strain sensor, the strain coefficient GF=1.41, the strain detection range is 25%~400%, the response time is 1.5-2 s, and the electrical signal output is stable after 1000 cycles of stretching.
[0013] Secondly, the present invention provides a method for preparing a strong and tough cellulose ion gel based on the ion shielding effect to enhance phase separation, comprising the following steps: (1) Mix AA acrylic acid, 1-ethyl-3-vinylimidazolium tetrafluoroborate, ethylene glycol EG, hydroxypropyl cellulose HPC, lithium tetrafluoroborate and photoinitiator according to the ratio and stir to obtain a uniform precursor solution; (2) Nitrogen gas was introduced into the precursor solution for 10 min for degassing treatment, and the gas flow was controlled to make the solution tumble and not splash. (3) The degassed precursor solution was injected into a polytetrafluoroethylene mold and polymerized by irradiation with 365 nm, 1300 mW ultraviolet light. After complete polymerization, cellulose ion gel was obtained.
[0014] Thirdly, this invention provides the application of strong and tough cellulose ionogels based on ion shielding effect-enhanced phase separation in flexible strain sensors, wearable human motion monitoring devices, electronic skin, and reversible adhesives.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses HPC as a supporting framework and lithium-ion-induced large-scale phase separation, which can synergistically regulate the fracture strength (15.1 MPa), tensile strength (515%), and toughness (45 MJ / m) of the ionogel. -3 ).
[0016] (2) The present invention endows cellulose ion gel with high-strength, reversible and temperature-tunable adhesion properties through the microphase separation structure formed by lithium ion induction and the abundant hydrogen bonds, ion-dipole and other non-covalent interactions in the system. The adhesion strength on glass can reach 4.26 MPa, and the adhesion strength does not decrease significantly after 50 cycles.
[0017] (3) The HPC of this invention can improve the conductivity of cellulose ion gel to 0.37 mS / cm by optimizing the ion transport channels. -1 Furthermore, it effectively improves its sensing performance, enabling the cellulose ionogel to exhibit a wide strain detection range of 25%–400% and a stable response, with a GF value of 1.41 and a response time between 1.5 and 2 seconds. Simultaneously, the cellulose ionogel demonstrates excellent cyclic stability, maintaining a stable electrical signal output even after 1000 cycles, showing potential for practical applications in wearable sensing. Attached Figure Description
[0018] The invention will now be further described with reference to the accompanying drawings.
[0019] Figure 1 Mechanical property optimization of cellulose ion gels: (a) Tensile curves of cellulose ion gels with different monomer contents; (b) Corresponding modulus and toughness; (c) Tensile curves of cellulose ion gels with different HPC contents; (d) Corresponding modulus and toughness; (e) Tensile curves of cellulose ion gels with different lithium ions; (f) Corresponding modulus and toughness. Figure 2 Fracture toughness of cellulose ionomers: (a) Elongation at break and fracture energy of cellulose ionomers with different HPC contents; (b) Elongation at break and fracture energy of cellulose ionomers with different lithium ion contents; (c) Notched tensile photographs of cellulose ionomers containing HPC and lithium ions at strains of 50%, 100%, and 300%, showing that they are not sensitive to crack propagation; (d) Notched tensile photographs of ionomers without HPC and lithium ions at strains of 20%, 50%, and 100%, showing that they are sensitive to crack propagation. Figure 3 Photos of cellulose ionogel being twisted, knotted, and supporting a 150 g weight; Figure 4 Cellulose ionogels are puncture resistant; Figure 5 Schematic diagram of the adhesion mechanism of cellulose ionogel; Figure 6 Adhesion strength of cellulose ionogels after heating to different temperatures and cooling to room temperature; Figure 7(a) Tensile curves of cellulose ionogel at different temperatures; (b) Corresponding modulus and toughness. The inset shows photographs of cellulose ionogel at different temperatures. Figure 8 Adhesion strength of cellulose ionogels on different substrates; Figure 9 Adhesion area S = 4 cm 2 Cellulose ion gel can easily lift a 28 kg bucket of water; Figure 10 Adhesion of cellulose ionogels at different temperatures; Figure 11 Cyclic adhesion of cellulose ionogels; Figure 12 A schematic diagram of the mechanism of phase separation inside lithium-ion-reinforced cellulose ion gel; Figure 13 (a) Photographs of the polymerization time of cellulose ion gels with different lithium ion contents; (b) Polymerization time of cellulose ion gels with different lithium ion contents; (c) SAXS of cellulose ion gels with different lithium ion contents; Figure 14 Electrical conductivity of cellulose ion gel: (a) Photograph of cellulose ion gel lighting a light bulb; (b) Effect of different HPC contents on the conductivity of cellulose ion gel; (c) Effect of different lithium ion contents on the conductivity of cellulose ion gel. Figure 15 Sensing properties of cellulose ion gel: (a) Change in relative resistance under different strains; (b) Change in relative resistance over time when cellulose ion gel is subjected to cyclic stretching under different tensile strains; (c) Change in relative resistance over time when cellulose ion gel is subjected to cyclic stretching at different stretching rates; (d) Response time and recovery time of cellulose ion gel. Figure 16 The change in relative resistance of cellulose ionogel after 1000 cycles of stretching; Figure 17 Sensing applications of cellulose ion gels: (a) Schematic diagram of monitored sensing locations; (b) Changes in relative resistance over time during cyclic stretching of the finger, (c) elbow, and (d) knee. Detailed Implementation
[0020] The invention will now be further described with reference to the accompanying drawings.
[0021] Experimental materials and chemical reagents Table 1 Main Experimental Instruments and Equipment .
[0022] Experimental instruments and equipment Table 2 Main Experimental Instruments and Equipment .
[0023] Experimental sample preparation All ionogels were prepared via free radical polymerization. The simplified steps are as follows: Acrylic acid (AA), 1-ethyl-3-vinylimidazolium tetrafluoroborate, ethylene glycol (EG), hydroxypropyl cellulose (HPC), lithium tetrafluoroborate, and a photoinitiator were mixed in a specific ratio and stirred to form a homogeneous precursor solution. Nitrogen gas was bubbled into the solution for 10 minutes for degassing, with the gas flow adjusted to ensure uniform turbulence without splashing. The solution was then injected into a polytetrafluoroethylene (PTFE) mold and polymerized under ultraviolet light (365 nm, 1300 mW). For example, an ionogel with a monomer ratio of AA:IL = 6:2, a cellulose content of 0.25 wt%, and a lithium ion content of 2M requires 3 g of AA, 1 g of IL, 2 g of ethylene glycol, 0.015 g of HPC, and 0.8 g of lithium tetrafluoroborate. Next, the above materials were mixed and stirred in air for 30 minutes, and the precursor solution was dropped onto a mold and polymerized under ultraviolet light to obtain the ionogel.
[0024] Sample testing and characterization (1) Mechanical performance testing Mechanical properties were tested using a universal testing machine (Hengyi, WDW-02, Jinan). The tensile specimens were cuboids with a length of 50 mm, a width of 7 mm, and a thickness of 3 mm, and the strain rate was 50 mm / min.
[0025] (2) Overlap shear test The bond strength was characterized by lap shear tests performed using a universal tensile testing machine. Before each test, the cellulose ionogel was trimmed into different sizes and placed between two substrates. The specimens were stretched vertically at a crosshead speed of 50 mm / min.
[0026] (3) Other testing methods The degree of phase separation in cellulose ionogels as a function of lithium ion content was characterized by small-angle X-ray scattering (SAXS, Xeuss 2.0, Xenocs, France).
[0027] Preparation and mechanical property optimization of cellulose ionogels A strong and conductive cellulose ionogel was prepared under ultraviolet light initiation by adjusting the ratio of AA and 1-ethyl-3-vinylimidazolium tetrafluoroborate (hereinafter referred to as ionic liquid or IL), the HPC content, and the lithium salt (Li⁺) concentration, using ethylene glycol as a solvent. Figure 1As shown in Figure a, with the HPC content fixed at 0.25 wt%, when the system contains no IL (i.e., AA:IL = 8:0), the cellulose ionogel exhibits typical rigid characteristics, with a tensile strength as high as 44.45 MPa, but an elongation at break of only 7.79%, indicating significant brittleness. As the IL content increases, the tensile strength of the cellulose ionogel gradually decreases, while the elongation at break significantly increases. When the AA:IL mass ratio is 6:2, although the tensile strength decreases to 3.74 MPa, the elongation at break increases dramatically to 600%, approximately 77 times higher than the pure AA system, achieving a transformation from rigidity to high toughness. Further increasing the IL content leads to incomplete dissolution of HPC in the system, preventing the formation of a uniform and stable gel network. Figure 1 The changes in modulus and toughness of b with the monomer mass ratio further confirm this rule. The Young's modulus of the ionogel shows a monotonically decreasing trend with the increase of IL content, continuously decreasing from 346 MPa in the pure AA system to 4.09 MPa in the 6:2 ratio, which fully demonstrates that IL plays an efficient plasticizing role in this system and achieves a significant improvement in gel toughness by enhancing the chain segment mobility.
[0028] Next, we selected a cellulose ionogel with a monomer ratio of 6:2 and systematically investigated the effect of HPC content on the mechanical properties of the ionogel. Figure 1 (c and 1d). The results showed that the introduction of HPC could simultaneously improve the tensile strength, elongation at break, and toughness of the ionogel. When the ionogel did not contain HPC, its mechanical properties were the worst, with tensile strength, modulus, and toughness of only 0.94 MPa, 1.2 MPa, and 2.5 MJ / m², respectively. -3 The elongation at break was only 464%; when the HPC content was increased to 0.25 wt%, the tensile strength and elongation at break of the ionogel increased to 3.83 MPa and 651%, respectively, while the modulus and toughness also increased to 4.09 MPa and 13.7 MJ / m², respectively. -3 This achieved a synergistic optimization of strength and toughness. This phenomenon can be attributed to the fact that HPC acts as a physical support framework, providing mechanical support for the gel network and enhancing the strength of the ionogel. On the other hand, the hydroxyl groups on the HPC molecular chain can form abundant dynamic hydrogen bonds and other non-covalent interactions with acrylic acid and the imidazole ring of the ionic liquid. While enhancing mechanical strength, the reversible breaking and rejoining of non-covalent bonds improves the extensibility of the polymer chain, endowing the gel with excellent tensile toughness. However, when the HPC content is further increased, the crosslinking density in the system continues to rise. Excessive physical crosslinking will restrict the mobility of the polymer chain, inhibit the deformation ability of the network, and ultimately lead to a decrease in the elongation at break. Therefore, 0.25 wt% is the optimal addition amount of HPC.
[0029] Besides monomer ratio and HPC content, lithium ion concentration is another key factor in regulating the structure and properties of ionogels. Figure 1 (e and 1 f). As the Li⁺ concentration increased from 0.5 M to 2 M, the tensile strength, modulus, and toughness of the ionogel all showed a trend of first increasing and then decreasing. When the Li⁺ concentration was 2 M, the overall mechanical properties of the ionogel reached their optimal levels, with tensile strength, modulus, and toughness reaching their peak values, while maintaining excellent elongation at break. However, when the Li⁺ concentration was further increased to 4 M, the mechanical properties deteriorated. This is because excessive Li⁺ may disrupt the hydrogen bonding interactions within the system and lead to ion aggregation, affecting the uniformity of the gel network. By systematically controlling the AA:IL monomer ratio, HPC content, and Li⁺ concentration, the mechanical properties of the ionogel can be optimized. Finally, the optimal formulation for the ionogel was selected as AA:IL = 6:2, HPC content 0.25 wt%, and Li⁺ concentration 2 M.
[0030] Stress concentration at the crack tip leading to catastrophic crack propagation is the core bottleneck causing irreversible fatigue fracture and significantly shortening the service life of flexible gel materials. To evaluate the crack propagation resistance of the prepared ionogel, this study systematically investigated the regulatory effects of hydroxypropyl cellulose (HPC) content and lithium ion (Li⁺) concentration on the fracture resistance of the ionogel using monotonic tensile tests with a single-sided notch (notch width accounting for 40% of the total sample width). The toughening mechanism was further revealed by combining in-situ tensile morphology characterization. Figure 2 As shown in Figure a, with the HPC addition gradually increasing from 0 wt% to 0.75 wt%, the crack propagation strain and fracture energy of the notched ionogel sample showed a significant synergistic increase trend. The crack propagation strain of the cellulose ionogel without HPC was only 100%, and the fracture energy was less than 2 kJ / m². -2 The crack propagation resistance is extremely poor. However, when the HPC content is increased to 0.75 wt%, the crack propagation strain increases significantly to 276%, and the fracture energy rises to 31.2 kJ / m². -2 This fully demonstrates that the introduction of HPC significantly enhances the crack propagation resistance of ionomer gels. Furthermore, we investigated the effect of Li⁺ concentration on fracture properties. Figure 2 (b) The results show that as the Li⁺ concentration increases from 0.5 M to 2 M, the crack propagation strain and fracture energy of the ionogel are continuously optimized. Under the 2 M Li⁺ condition, the fracture energy is further increased to 37 kJ / m². -2 The crack propagation strain reached over 300%, achieving further enhancement of fracture resistance. However, when the Li⁺ concentration was too high, reaching 4 M, the fracture energy showed a slight decrease. This was due to the phase separation imbalance caused by excessive ions, which led to a decrease in network uniformity.
[0031] The tensile diagram of cellulose ionogels visually demonstrates the differences in their mechanical properties. Figure 2 c represents the tensile process of the notched specimen with added HPC and Li⁺. As the strain gradually increases from 50% to 300%, the notch tip of the specimen continuously blunts and gradually rounds, with no significant crack propagation. Even at 300% strain, the specimen maintains its intact structure, demonstrating excellent crack suppression capability. This contrasts sharply with the ionomer gel without added HPC and Li⁺ (…). Figure 2 d) At only 20% strain, the notch showed significant propagation; at 50% strain, the crack tip continued to sharpen; and at 100% strain, the crack length extended to 2 / 3 of the original notch, ultimately leading to rapid fracture failure. This indicates that the introduction of HPC significantly increased the crosslinking density of the ionogel, constructing a denser physical crosslinking network. Under external tensile loads, the HPC framework can effectively transfer stress, while simultaneously achieving efficient energy dissipation through non-covalent interactions such as dynamic hydrogen bonds between molecular chains. This fundamentally alleviates stress concentration at the crack tip and prevents rapid crack propagation. Furthermore, the introduction of Li⁺ enhances the aggregation of polymer chains through the ion shielding effect, further optimizing the phase separation structure of the network. This allows stress to be more uniformly distributed within the network, avoiding crack initiation and propagation caused by localized stress overload. The synergistic effect of these two factors endows the ionogel with excellent crack propagation resistance and fatigue resistance.
[0032] Figure 3 The prepared ionogel exhibits excellent mechanical flexibility and structural integrity. As shown in the figure, the ionogel sample can freely undergo various extreme deformation operations such as twisting, bending, and knotting in its initial state. During repeated bending and knotting, the material maintains its structural integrity without significant cracking or fracture failure, demonstrating excellent plasticity and deformation capacity. More importantly, even under large tensile deformation, the ionogel maintains its intact overall structure without localized damage or macroscopic fracture. Furthermore, its excellent load-bearing capacity is confirmed by stably suspending a 1500 g (750 g × 2) weight load using a single ionogel strip. Under the combined effects of large load and large deformation, the cellulose ionogel network maintains a stable structure without relaxation or fracture. All of this indicates that the ionogel possesses both excellent flexibility and high strength load-bearing characteristics.
[0033] Furthermore, the excellent toughness of ionogels gives them puncture resistance. For example... Figure 4As shown, when a needle is applied to the ionogel, the gel does not puncture, form holes, rupture, or experience structural collapse. It only exhibits slight elastic deformation at the contact area and is highly likely to return to its original shape after the external force is removed, demonstrating its resistance to needle puncture. This is attributed to the phase separation mechanism within the cellulose ionogel, which provides an effective energy dissipation area. This allows the gel to disperse local stress through phase aggregation regions upon needle contact, rather than being directly punctured, exhibiting excellent deformation recovery and resistance to puncture damage.
[0034] Reversible adhesion of cellulose ion gels like Figure 5 As shown, due to the abundance of carboxyl and hydroxyl groups as well as lithium bonds, ionogels can form strong interactions with a variety of substrates, which is the key to improving the interfacial adhesion of cellulose ionogels.
[0035] The reversible viscosity of ionogels is controlled by a heating-cooling cycle, therefore, Figure 6 The adhesive strength of ionomers was quantitatively evaluated using lap shear tests after heating to different temperatures and then cooling to room temperature (unless otherwise specified, all adhesive strength tests were performed on a glass substrate). As shown in the figure, the adhesive strength of the ionomers increases with increasing heating temperature. Below room temperature, especially below 0 °C, the ionomers exhibit no adhesiveness. However, when the ionomers are heated above room temperature and then cooled to room temperature, their adhesiveness gradually increases. The highest adhesive strength of the ionomer on the substrate, 4.26 MPa, is achieved when the heating temperature reaches 60 °C. This can be attributed to the softening of the ionomer after heating, allowing for better wetting of the substrate.
[0036] like Figure 7 As shown in Figure a, the tensile strength at break of cellulose ionomer decreases while the tensile breaking ratio increases with increasing temperature. Simultaneously, the modulus of cellulose ionomer can also be calculated from the curve, as shown in Figure a. Figure 7 As shown in b. Based on this thermal softening property, cellulose ionomer gels can achieve strong adhesion by varying the heating temperature to ensure full bonding with the substrate. In summary, the phase-separated structure within the cellulose ionomer gel increases the overall cohesive energy through energy dissipation, maintaining the cellulose ionomer gel bulk intact during adhesion-deadlock processes. The thermal softening property ensures sufficient wetting of the substrate. Furthermore, the high-density polymer phase on the surface enhances the physical interaction with the substrate, thereby increasing interfacial adhesion.
[0037] Therefore, ionomers exhibit excellent bonding strength on a variety of substrates, such as glass, wood, iron sheets, and PMMA (…). Figure 8As can be seen, the ionogel exhibits the strongest adhesion strength on glass, reaching 4.26 MPa, followed by 2.6 MPa on wood. Due to the low surface energy of polytetrafluoroethylene (PTFE), the adhesion strength on PTFE sheets is relatively weak (0.99 MPa). This indicates that the ionogel demonstrates stronger adhesion on hydrophilic surfaces.
[0038] like Figure 9 As shown, the area is only 2 cm. 2 The cellulose ion gel sample was able to lift a 28 kg bucket of water, and during the lifting process, the cellulose ion gel did not detach or become damaged, demonstrating excellent adhesion properties.
[0039] Due to the temperature sensitivity of cellulose ionogels, their bonding strength can be adjusted by temperature, such as... Figure 10 As shown, the bonding strength of the cellulose ionomer gel bonded to the substrate was tested after being placed at different temperatures for 24 hours. At -20℃, the cellulose ionomer gel showed almost no adhesion to the glass substrate. As the temperature increased to room temperature (20℃), the bonding strength gradually increased to 4.26 MPa. However, with further increases in temperature, the adhesion of the cellulose ionomer gel gradually decreased. Therefore, this fully demonstrates that cellulose ionomer gel can be bonded and debonded by heating.
[0040] In addition, to characterize the cyclic adhesion properties of the cellulose ionogel, a 50-cycle adhesion test was conducted. Figure 11 As shown, the adhesion of cellulose ionogel to the glass substrate showed no obvious fatigue or attenuation. After 50 cycles of adhesion, it still maintained an adhesion strength of about 4 MPa, indicating that the ionogel adhesive has good reusability.
[0041] Mechanistic study of cellulose ion gel The abundant non-covalent interactions within ionogels are a key factor contributing to their superior performance; therefore, the internal network structure of ionogels has been investigated. For example... Figure 12 The diagram shown is a schematic of the interactions within an ionogel.
[0042] In this process, the carboxylate ions on acrylic acid maintain the extended state of the polymer chains due to electrostatic repulsion. With the addition of lithium salt, the positive charge of lithium ions neutralizes the negative charge of carboxylate ions, and this electrostatic shielding leads to the aggregation of polymer chains within the ionogel. During polymerization, the increased lithium salt content enhances the electrostatic shielding effect, increasing the degree of polymer chain aggregation. This results in the encapsulation of some key functional groups, such as double bonds, hindering polymerization. The aggregated polymer chains form aggregation regions within the system, providing an effective stress dispersion area for the ionogel under deformation and preventing excessive stress concentration. Furthermore, HPC acts as a supporting framework within the system. This is mainly due to its unique molecular structure and excellent compatibility with the ionic medium environment. HPC molecular chains contain numerous hydroxyl and hydroxypropoxy groups, which can form hydrogen bonds and ion-dipole interactions with ionic liquids and ionic components, thus forming a continuous, dense three-dimensional network structure. Simultaneously, it can maintain the extended state of the molecular chains in a high-ionic environment. In addition, HPC and ionic liquids can also form microphase separation structures, providing excellent mechanical support for the ionogel.
[0043] Figure 13 Experiments demonstrated the different polymerization times of ionogels with varying lithium salt contents. It was observed that when the ionogel contained no lithium salt, it began to yellow after 60 seconds of UV irradiation, indicating the start of polymerization, and was fully polymerized after 90 seconds. With increasing lithium salt content, the ionogel with a 2 M lithium ion content required 150 seconds to fully polymerize, while the ionogel with a 4 M lithium ion content required 180 seconds. This indicates that the presence of lithium ions hinders the polymerization of the ionogel. More detailed polymerization times can be found in [the following section / reference]. Figure 13 b. To investigate how lithium ions affect the polymerization of ionogels and the source of their excellent mechanical and adhesive properties, SAXS characterization was performed. Figure 13 As shown in Figure c, the scattering peaks of all ionogels with lithium ion content are very obvious, including the ionogel with zero lithium ion content. This indicates that phase separation exists in the system before the introduction of lithium ions, and this phase separation is caused by the immiscibility between HPC and the ionic liquid. With the addition of lithium salt, the peak intensity of the scattering peak gradually increases, and the position of the scattering peak gradually shifts towards smaller q values. This indicates that after the addition of lithium salt, the degree of phase entanglement and the aggregation region inside the ionogel both increase. This fully demonstrates that after the addition of lithium salt, the degree of phase separation inside the cellulose ionogel increases, providing an energy dissipation mechanism for dispersing stress during deformation, and effectively balancing the cohesive energy and interfacial adhesion energy of the cellulose ionogel.
[0044] Conductivity and Sensing Applications of Cellulose Ion Gels Besides its excellent and stable mechanical properties and superior adhesion characteristics, outstanding ionic conductivity is a core prerequisite for ionogels to function as flexible strain sensors. For example... Figure 14 As shown in Figure a, when the ion gel material is connected to a closed circuit containing an LED, the device can be quickly lit up, displaying a bright green light. This intuitively and directly proves that the ion gel system has efficient ion transport capabilities and good conductivity, providing the necessary electrical basis for its application in flexible electronic devices.
[0045] To further quantify and evaluate the regulatory effect of HPC content on the conductivity of ionogels, the ionic conductivity under different HPC addition amounts was systematically tested. The results are as follows: Figure 14 As shown in b, in lithium-free cellulose ionogels, the conductivity of the ionogels showed a significant increasing trend from 0 to 0.25 wt%, from 0.14 mS / cm. -1 It rose sharply to approximately 0.37 mS cm -1 The improvement was approximately 2.6 times. This can be attributed to the precise control of the microphase separation structure within the ionogel by HPC.
[111] Specifically, HPC molecular chains, through dynamic non-covalent interactions with components within the system, guide the reconstruction and optimization of ion transport pathways, promoting the formation of a more continuous, dense, and interconnected three-dimensional network structure of internal ion channels. This highly interconnected ion transport network significantly reduces the ion transport barrier, thereby efficiently improving conductivity. However, when the HPC content further increases to 0.5 wt% or higher, the conductivity begins to decline. This is because excessive HPC significantly increases the crosslinking density and physical compactness of the gel network. While effectively enhancing the mechanical strength of the material, the overly dense network structure exerts a significant steric hindrance effect on ion migration, limiting the movement rate of free ions and ultimately leading to a decrease in overall conductivity.
[0046] Meanwhile, lithium ion (Li⁺) concentration, as a key factor affecting ion migration, influences the regulation of conductivity as follows: Figure 14 As shown in c. With the HPC content fixed at 0.25 wt%, as the Li⁺ concentration gradually increased from 0.5 M to 2 M, the conductivity of the ionogel increased from 0.3 mS / cm. -1 Decreased to 0.17 mS cm -1This is mainly attributed to the enhanced electrostatic shielding effect. High concentrations of Li⁺ interact strongly with the charged sites on the polymer chains, effectively shielding the electrostatic repulsion between polymer chains, leading to polymer chain aggregation and contraction. This aggregation not only restricts the migration freedom of free Li⁺ but also disrupts some continuous ion transport channels, resulting in a decrease in conductivity with increasing ion concentration. When the Li⁺ concentration is further increased to 4 M, the conductivity shows a slight rebound. This may be because the excessively high Li⁺ concentration results in a large number of "free" unbound ions in the system. Although the polymer chains collapse to some extent due to electrostatic shielding, the significant increase in the number of free ions compensates for the negative impact of blocked transport paths to some extent, ultimately leading to a slight upward trend in conductivity. Therefore, the conductivity of ion gels is jointly determined by the HPC content and lithium ion concentration through the regulation of the microstructure and ion transport behavior. By optimizing the HPC content and lithium ion concentration, a synergistic balance between mechanical strength and ion conductivity can be achieved.
[0047] Sensitivity is a key performance indicator for wearable strain sensors, typically quantitatively characterized by the Gauge Factor (GF), defined as the ratio of the relative resistance change rate (ΔR / R0 = (R-R0) / R0) to the applied strain. It directly reflects the sensor's ability to efficiently convert mechanical deformation into an electrical signal. Figure 15 As shown in Figure a, the cellulose ionogel prepared in this study exhibits excellent strain-sensitive response characteristics over a wide strain range. Within the 0-300% strain range, the relative resistivity change rate shows a highly linear positive correlation with strain. The strain coefficient GF, calculated through fitting, is 1.41 for this range, indicating that the sensor possesses stable and repeatable signal response capabilities in the low to medium strain range. When the strain is further increased to the large strain range of 300%-400%, although the GF value decreases slightly to 1.27, it still maintains good linear response and signal sensitivity, fully demonstrating that the ionogel possesses stable strain-to-electrical signal conversion capabilities over an ultra-wide strain range.
[0048] To further verify the reliability of the sensor in practical applications, the system underwent cyclic response testing of multiple strain amplitudes. Figure 15 (b) During strain cycles of 25%, 50%, 100%, 200%, 300%, and 400%, the relative resistance response signal of the ionogel sensor exhibits highly synchronized periodic changes with the strain amplitude. The signal shows no significant baseline drift or amplitude attenuation, and the response amplitude in different strain ranges increases regularly with increasing strain. This demonstrates that the sensor possesses excellent strain recognition capability and cyclic stability, accurately capturing different degrees of mechanical deformation and achieving stable signal output over a wide strain range.
[0049] Based on this, the effect of stretching rate on sensing performance was further investigated. Figure 15 c). At 50 mm min -1 100 mm min -1 150 mm min -1 200 mm min -1 Under different stretching rates, the peak value of the relative resistance response of the ionogel remains highly consistent and has no obvious rate dependence, indicating that its sensing performance is not affected by the stretching speed. It has excellent adaptability and anti-interference ability to the dynamic changes of external load, which meets the adaptation requirements of wearable devices for different action rates in human motion monitoring.
[0050] Furthermore, rapid response and recovery capabilities are core requirements for wearable sensing devices to achieve real-time monitoring. Only with extremely fast signal response speeds can the dynamic changes in human activity be captured accurately and without delay. Therefore, the response time and recovery time of the ionogel were tested. Figure 15 d) The results showed that the ionogel had a response time of only 1.5s and a recovery time of 2s, exhibiting extremely fast electrical signal response and rebound capability. It can capture the dynamic changes of mechanical deformation in real time and accurately, providing a solid performance guarantee for the real-time monitoring of human movement and physiological signals.
[0051] To systematically evaluate the fatigue stability of the prepared ionogel sensor, this study conducted a continuous cyclic tensile test of up to 1000 cycles under a constant strain of 50%, comprehensively characterizing the long-term stability of its electrical signal response and structural reliability.
[0052] like Figure 16 As shown, during 1000 cycles of stretching, the relative resistance change rate ((R-R0) / R0) of the ionogel sensor remained stable at approximately 55%, with no significant baseline drift or amplitude attenuation in the output electrical signal. The peak and trough values of the response curve highly overlapped, demonstrating excellent cyclic stability and fatigue resistance. The magnified views of the typical intervals of 210-240 s and 770-800 s in the inset further confirm that the ionogel exhibits no signal distortion and no performance degradation, fully demonstrating its extremely strong repeatability and reliability in electrical signal output under long-term cyclic loading.
[0053] To comprehensively evaluate the practical application potential of the prepared ion gel flexible sensor in the field of wearable human motion monitoring, this study attached the ion gel sensor to typical motion joints such as the elbow and knee of the human body. By collecting the relative resistance change signal in real time, the system verified its monitoring ability and response characteristics of the human body's dynamic reciprocating motion. The results are shown in the figure.
[0054] like Figure 17 As shown in Figure a, ion gel sensors were fixed to the subject's hand, elbow, and knee joints, respectively, and the electrical signal responses during the subject's continuous reciprocating movements such as bending fingers, swinging arms, and bending knees were recorded simultaneously. Figure 17 bd corresponds to the real-time resistance change curves of finger, elbow, and knee joint movements, respectively. The results show that throughout the entire reciprocating motion, the ionogel sensor outputs highly stable and regular periodic relative resistance change signals, fully demonstrating that the sensor has excellent electrical signal reversibility and real-time response capability, and can accurately capture the dynamic deformation process of human joints.
[0055] The above results fully demonstrate that the flexible sensor constructed based on this ion gel has excellent real-time responsiveness, signal stability and motion state recognition capabilities, showing broad application prospects in fields such as electronic skin, human health monitoring and motion posture capture.
Claims
1. A strong and resilient cellulose ionogel based on ion shielding effect to enhance phase separation, characterized in that, The tough cellulose ion gel is prepared by ultraviolet-radical polymerization of monomer components AA acrylic acid, 1-ethyl-3-vinylimidazolium tetrafluoroborate ionic liquid, ethylene glycol EG, hydroxypropyl cellulose HPC, lithium tetrafluoroborate, and a photoinitiator. The ion gel uses HPC as the backbone and acrylic acid and vinyl ionic liquid as polymer chains. The phase separation structure of the system is strengthened by the ion shielding effect generated by lithium ions, thereby achieving synergistic optimization of mechanical properties, adhesion properties, and conductive sensing properties.
2. The strong and tough cellulose ionogel based on ion shielding effect to enhance phase separation according to claim 1, characterized in that, The proportions of each raw material are as follows: the mass ratio of acrylic acid to 1-ethyl-3-vinylimidazolium tetrafluoroborate is 6:2, the amount of HPC added is 0.25 wt% of the total mass of the system, the lithium ion concentration is 2M, and the molar concentration of lithium tetrafluoroborate is 2M.
3. The strong and tough cellulose ionogel based on ion shielding effect to enhance phase separation according to claim 1, characterized in that, The photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone.
4. The strong and tough cellulose ionogel based on ion shielding effect to enhance phase separation according to claim 2, characterized in that, The raw material components are as follows: ethylene glycol, the solvent, accounts for 33.33% of the total mass of the solute and solvent, i.e., the mass ratio of ethylene glycol to the total mass of the solute ionic liquid IL and acrylic acid AA is 1:2; the lithium tetrafluoroborate concentration is 2M; and the photoinitiator accounts for 1% of the total mass of AA (in IL) and the total mass of monomer AA + IL. The strong cellulose ionic gel based on ion shielding effect to enhance phase separation according to claim 2 is characterized in that the raw material components are: 3 g of AA, 1 g of 1-ethyl-3-vinylimidazolium tetrafluoroborate IL, 2 g of ethylene glycol, 0.015 g of HPC, 0.8 g of lithium tetrafluoroborate, and 0.04 g of photoinitiator.
5. The strong and tough cellulose ionogel based on ion shielding effect to enhance phase separation according to claim 1, characterized in that, The mechanical properties of the cellulose ion gel are as follows: fracture stress 15.1 MPa, fracture strain 515%, and fracture toughness 45 MJ·m⁻³. It has the characteristics of crack propagation resistance, torsion resistance, knotting resistance, and puncture resistance. The notched sample showed no obvious crack propagation at 300% strain.
6. The strong and tough cellulose ionogel based on ion shielding effect to enhance phase separation according to claim 1, characterized in that, The cellulose ion gel exhibits temperature-controlled reversible adhesion properties. When heated to 60 °C and cooled to room temperature, it achieves an adhesion strength of 4.26 MPa on a glass substrate. It also exhibits adhesion capabilities on wood, iron sheets, PMMA (polymethyl methacrylate), and polytetrafluoroethylene substrates, maintaining an adhesion strength of 4 MPa after 50 adhesion cycles.
7. The strong and tough cellulose ionogel based on ion shielding effect to enhance phase separation according to claim 1, characterized in that, The cellulose ion gel has an electrical conductivity of 0.37 mS·cm⁻¹; when used as a strain sensor, the strain coefficient GF=1.41, the strain detection range is 25%~400%, the response time is 1.5-2 s, and the electrical signal output is stable after 1000 cycles of stretching.
8. The method for preparing a strong and tough cellulose ionogel based on ion shielding effect to enhance phase separation according to any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Mix AA acrylic acid, 1-ethyl-3-vinylimidazolium tetrafluoroborate, ethylene glycol EG, hydroxypropyl cellulose HPC, lithium tetrafluoroborate and photoinitiator according to the ratio and stir to obtain a uniform precursor solution; (2) Nitrogen gas was introduced into the precursor solution for 10 min for degassing treatment, and the gas flow was controlled to make the solution tumble and not splash. (3) The degassed precursor solution was injected into a polytetrafluoroethylene mold and polymerized by irradiation with 365 nm, 1300 mW ultraviolet light. After complete polymerization, cellulose ion gel was obtained.
9. The application of the strong and tough cellulose ionogel based on the ion shielding effect to enhance phase separation as described in any one of claims 1 to 8 in flexible strain sensors, wearable human motion monitoring devices, electronic skin, and reversible adhesives.